Role of Political Education in Improving Public Participation in Election: The Case ofWest Sumatera Governor Election - ., Pebriyenn; Ananda, Azwar; Gistituati, Nurhizrah (International Journal of Engineering and Technology, 2018)
This article describes the role of political education to improve public participation in the election of West Sumatra governor. The governor election is expected to be able to raise the level ofoptimism in order to improve the leadership qualities of local government, and the spirit of political education for citizen. This study applied descriptive qualitative method by using interviews and documentations as research instruments. Based on the documentation instrument, it showed the statistics of permanent voters who voted in the 2015 for governor election was 59.58% or 3,489,743 permanent voters. It was implied that 40.42% or 1,410,680 voters did not take their votes. This low level of public participation could be a sign that democracy has not effectively been implemented at the local level. The researchers concluded that the socialization activities of Governor election, as one of responsibilities of General Election Commission, have failed to increase the political awareness of the society. Â Â